Implementation of Problem Based Learning Model in Energy Material to Enhance Critical Thinking Skills of Grade VI Students at SDN Kauman 1 Malang - Putri Fauzi, Aprilia Aurely; Restian, Arina; Ismanto, Puguh Hadi (J-SES : Journal of Science, Education and Studies, 2025)
This classroom action research aims to enhance the critical thinking skills of grade VI students at SDN Kauman 1 Malang through the implementation of the Problem Based Learning (PBL) model on energy topics. This research employs a quantitative approach with a classroom action research design conducted in two cycles. The research subjects were 28 grade VI students of SDN Kauman 1 Malang in the academic year 2024/2025. Data on students' critical thinking skills were collected through written tests in the form of essay questions before and after the action in each cycle. Data analysis was performed using descriptive quantitative methods to observe the improvement in the average critical thinking skills scores of students between cycles. The research results indicate an improvement in students' critical thinking skills after the implementation of the PBL model.